2019
DOI: 10.5433/1679-0359.2019v40n3p1165
|View full text |Cite
|
Sign up to set email alerts
|

Profitability analysis of compost barn and free stall milk-production systems: a comparison

Abstract: The objective of this study was to comparatively analyse the profitability of compost barn and free stall milk-production systems as a means of helping producers and technicians choose the type of facility most suitable for each farm. Data collected from four farms from January to December 2016 were analysed; the data were distributed equally among compost barn and free stall systems. The cost of milk production was estimated according to the operating cost methodology and considering the milk production cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 30 publications
(43 reference statements)
2
13
2
Order By: Relevance
“…The average of total fixed assets, without land and animal values, was R$ 6,353,700.50 in 2016 and 2017 (Table 1). It corresponded to 45.19% of the investments made on the farm and very similar to that of the study of Silva et al (2019) (46.74%).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The average of total fixed assets, without land and animal values, was R$ 6,353,700.50 in 2016 and 2017 (Table 1). It corresponded to 45.19% of the investments made on the farm and very similar to that of the study of Silva et al (2019) (46.74%).…”
Section: Resultssupporting
confidence: 83%
“…Milk yield had the greatest contribution to total revenue (95.48 and 95.14% in 2016 and 2017, respectively). These were above the 93.15% observed by Silva et al (2019), but below the 98.16% by Santos andLopes (2012, 2014). Moreover, sales of biofertilizers had an average contribution of 2.415%.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Brito (2016) found that construction costs for CBP in Brazil were R$4,275.69 (R$1 = US$0.24). More recently, Silva et al (2019) analyzed capital invested in Brazilian dairy farms and showed that farms with CBP have a lower percentage of total capital invested in farm facilities than those with FS (55.31% vs. 58.79%). In the same study, the mean construction costs for CBP and FS were reported to be R$3,501.10 and R$3,763.11 per cow place, respectively.…”
Section: Economicsmentioning
confidence: 99%
“…Brito (2016), in Brazilian CBP, observed values from R$30.00 to R$38.00 spent on bedding per animal housed per month. Silva et al (2019) compared the contribution of bedding cost with the total production cost of milk in Brazil and found that CBP farms had a higher bedding cost contribution than FS farms (1.49% vs. 0.42%).…”
Section: Economicsmentioning
confidence: 99%